Microbial Community Structure and Function of Soil Following Ecosystem Conversion from Native Forests to Teak Plantation Forests - de Gannes, Vidya; Bekele, Isaac; Dipchansingh, Denny; Wuddivira, Mark N.; De Cairies, Sunshine; Boman, Mattias; Hickey, William J. (Frontiers in Microbiology, 2016)
Soil microbial communities can form links between forest trees and functioning of forest soils, yet the impacts of converting diverse native forests to monoculture plantations on soil microbial communities are unknown. This study tested the hypothesis that conversion from a diverse native to monoculture ecosystem would be paralleled by a reduction in the diversity of the soil microbial communities. Soils from Teak (Tectona grandis) plantations and adjacent native forest were examined at two locations in Trinidad. Microbial community structure was determined via Illumina sequencing of bacterial 16S rRNA genes and fungal internal transcribed spacer (ITS) regions, and by phospholipid fatty acid (PLFA) analysis. Functional characteristics of microbial communities were assessed by extracellular enzyme activity (EEA). Conversion to Teak plantation had no effect on species richness or evenness of bacterial or fungal communities, and no significant effect on EEA. However, multivariate analyses (nested and two-way crossed analysis of similarity) revealed significant effects (p < 0.05) of forest type (Teak v. native) upon the composition of the microbial communities as reflected in all three assays of community structure. Univariate anaylsis of variance identified two bacterial phyla that were significantly more abundant in the native forest soils than in Teak soils (Cyanobacteria , p = 0.0180; Nitrospirae, p = 0.0100) and two more abundant in Teak soils than in native forest (candidate phyla TM7, p = 0.0004; WS6, p = 0.044). Abundance of an unidentified class of arbuscular mycorrhizal fungi (AMF) was significantly greater in Teak soils, notable because Teak is colonized by AMF rather than by ectomycorrihzal fungi that are symbionts of the native forest tree species. In conclusion, microbial diversity characteristics were not affected in the conversion of native forest to teak plantation, but examination of specific bacterial taxa showed that there were significant differences in community composition.